Effect of Taper and Pitch on Nickle-Titanium File with Variable Cross Section to Its Cyclic Fatigue (In Silico Study) - Chrysandra, Yustika; Nugraheni, Tunjung; Hadriyanto, Wignyo (Journal of Dentistry Indonesia, 2024)
The geometric design of an endodontic file includes cross-sectional shape, taper, and pitch. NiTi endodontic files of OneCurve (MicroMega) are made of two variations of cross-sectional shape, that is, double-s shaped and triple helix. Various kinds of modifications were made to increase the resistance of the NiTi endodontic files from fracture. Cyclic fatigue is the most common factor that causes a fracture of the endodontic file. Objective: The purpose of this study was to obtain a NiTi endodontic file design that has the best cyclic resistance value based on its taper size and number of pitch. Methods: This study used OneCurve endodontic file size 25.06, then scanned with MicroCT Scan and modified the geometric design. The number of file modifications was nine. Taper size modifications were 4%, 6%, and 8%; the number of pitch modifications was reduced by three, fixed, and added by three. Cyclic fatigue measurement simulations were carried out using the finite element method three times each. The result data were analyzed using a two-way ANOVA test and then continued with LSD. Results: The results of the statistical test showed that there was an effect of the size of the taper on the cyclic fatigue values. Endodontic files with a size of a taper 4% had the lowest cyclic fatigue value. Conclusion: The conclusion of this research was that the taper size affects the value of cyclic fatigue in continuous endodontic files made of nickel-titanium with variable cross sections. The number of pitch did not show a significant effect on the cyclic value.